Professional Ethics in Accounting as Assessed by Managers of Entities - Voss, Grażyna (European Journal of Economics and Business Studies, 2018)
The code of professional ethics in accounting constitutes a collection of ethical standards, the observation of which is an indispensable part of contemporary accounting. Their scope and practical use give rise to no doubts, and for this reason all necessary measures must be taken to ensure their correct and common application. The evaluation of the practical application of ethical standards in accounting as assessed by managers of organisational units gives rise to doubts and therefore the role of professional ethics must be strengthened by means of actions to promote and educate or to apply directly precautionary measures and the ones confirming the observation of ethical standards by units. However, introduction of such solutions requires a change in legal regulations and in the approach in all the business entities operating on the market.